Cubeo Hehénewa religious thought : metaphysics of a northwestern Amazonian people - Goldman, Irving, 1911-2002 (Columbia University Press, 2004)
The societies of Vaupes region are among the most documented indigenous cultures, in part because they are thought to resemble earlier civilizations lost during initial colonial conflict, and students and scholars are eagerly awaiting the publication of this posthumous work by the man widely regarded as the preeminent authority on Vaupes Amazonian societies. Cubeo Hehenewa Religious Thought will be the definitive account of the religion of a significant Amazonian culture. Cubeo religious thought is truly a philosophy that incorporates ideas about the nature of the cosmos, society, and human life; the individual's orientation to the world; the use of hallucinogenic substances; and mystical dimensions akin to certain ideas of Eastern religions. This volume was substantially completed before Irving Goldman's death, but Peter Wilson has edited it for publication, providing an introduction to Goldman's work. Stephen Hugh-Jones has contributed an afterword, setting the work in the context of Vaupes ethnography.